PROFIL LAPISAN PEMAHAMAN KONSEP TURUNAN FUNGSI DAN FOLDING BACK MAHASISWA CALON GURU MATEMATIKA BERDASARKAN GENDER (Universitas Dr. Soetomo, 2016)
This research aimed to describe the profile of understanding layers of understanding the concept of the function’s derivative and folding back college student prospective teachers of mathematics by gender. This study used a qualitative descriptive approach . The data obtained is validated, then the analysis step-by- step reduction, data presentation, categorization, interpretation and inference. The analysis process is guided to the understanding of the model which hypothesizes Pirie&Kieren owned eight layers understanding students. The results showed that there was no difference between the achievement of a layers of understanding of the subject of women and man, both of them have an indicator layers of understanding ie; primitive knowing, image making, image having, property noticing, formalising, observing and structuring, then reaching also the first indicator (In1) of inventising layer, and indicators